EXPLORING HOW A VIRTUAL CHICKEN GROWTH SIMULATOR SPARKS CURIOSITY IN AGRICULTURE STUDIES AMONG STUDENTS IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the impact of a Virtual Chicken Growth Simulator (VCGS) on fostering curiosity in agriculture studies among secondary school students in Cross River State, Nigeria. With agriculture being a cornerstone of Nigeria’s economy, yet facing declining interest among youth, innovative educational tools like VCGS offer a promising avenue to engage students. Using a primary data collection method, a survey was conducted with 300 students across five secondary schools in Calabar, employing a mixed-methods approach with questionnaires and focus group discussions. The Technology Acceptance Model (TAM) served as the theoretical framework, assessing perceived usefulness and ease of use as predictors of curiosity. Results indicate that 78% of students reported heightened curiosity about poultry farming after using VCGS, with a statistically significant correlation (r = 0.65, p < 0.05) between simulator use and interest in agriculture studies. Qualitative findings reveal that interactive features, such as real-time growth tracking and problem-solving scenarios, were key motivators. Gender differences showed males (82%) slightly more curious than females (74%), though both groups valued the simulator’s practical relevance. The study underscores VCGS’s potential to bridge theoretical learning and practical agricultural engagement, recommending its integration into the curriculum and further development with local content.